Management Of Improving Reproductive Healthy Lifestyle In Students' Environment Subang District Junior High School - Marliana Rahma; Achmad Sanusi; Fahruroji; Nandang Koswara (International Journal of Science, Technology & Management, 2022)
The Maternal Mortality Rate in Indonesia is still high, the number of cases of maternal mortality in Subang Regency is also still far from the achievement target. One of the causes of maternal death in Subang Regency is in the adolescent phase. Lack of knowledge of adolescents about reproductive health becomes an important point and has a widespread impact on women's health conditions in the future. This study aims to determine and analyze how the management of improving reproductive healthy lifestyles at SMPN 1 Subang, SMPN 2 Subang and SMPN 4 Subang. This research uses a qualitative approach with a case study method, the sample is determined purposively with key informants the principal, vice principal of curriculum, science subject teachers, PMR coaches and students. The research location is at SMPN 1 Subang, SMPN 2 Subang and SMPN 4 Subang. Data were obtained from in-depth interviews, document materials, and participant observation. The findings of this study are: 1) Goals and Programs for Improving Reproductive Healthy Lifestyles among students in 3 locations of SMP Negeri Subang, starting with the science education curriculum for grade IX students; 2) Implementation of the Reproductive Healthy Lifestyle Improvement Program in 3 SMP N Subang in the form of implementing learning activities in science subjects. In its implementation, the program to improve reproductive health is carried out through science learning, in collaboration with local health centers for the program of giving blood-added tablets, in collaboration with the health office in providing reproductive health counseling; 3) Problems in implementing the program to improve reproductive healthy lifestyles are teaching materials that are less relevant to the goal of reducing maternal mortality, consumption of blood-added tablets is not monitored properly, health education is not routinely given. 4) Solutions to problems in implementing programs to improve reproductive healthy lifestyles: adding teaching materials, monitoring and evaluating adherence to consuming blood-added tablets, and increasing reproductive health counseling activities. The product of this research is the adolescent reproductive health module for junior high school students.